2022
DOI: 10.3390/jcm11030485
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a Trichinellosis Outbreak in Poland after Consumption of Sausage Made of Wild Boar Meat

Abstract: An outbreak of trichinellosis due to the consumption of sausage made from wild boar meat unexamined for the presence of Trichinella spp. was reported in Poland in December 2020. The outbreak affected eight people. Examination of the sausages made of wild boar meat collected during epidemiological investigation indicated a high level of Trichinella spp. Larvae per gram (>30 lpg) and therefore the threat of an infection in humans after consumption of such product was significant. Over the years, the main sour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…In Europe, wild boar meat has been responsible for many reported human outbreaks and is considered an important source of human trichinellosis, along with pork meat. Recreational hunting and consumption of undercooked wild boar meat have increased the risk of acquiring trichinellosis, especially for hunters, their families and friends [2,[40][41][42]. In the present study, we found that pork and wild boar-consumed meat products came from non-commercial sources or privately raised animals.…”
Section: Discussionmentioning
confidence: 48%
“…In Europe, wild boar meat has been responsible for many reported human outbreaks and is considered an important source of human trichinellosis, along with pork meat. Recreational hunting and consumption of undercooked wild boar meat have increased the risk of acquiring trichinellosis, especially for hunters, their families and friends [2,[40][41][42]. In the present study, we found that pork and wild boar-consumed meat products came from non-commercial sources or privately raised animals.…”
Section: Discussionmentioning
confidence: 48%
“…Nevertheless, our results suggest that both syl- as the source of infection (Messiaen et al, 2016). Other human outbreaks associated with consumption of wild boar meat have been widely reported worldwide (De et al, 2015;Holzhauer et al, 2014;Kim et al, 2011;Rózycki et al, 2022).…”
Section: Discussionmentioning
confidence: 55%
“…In addition, a major human outbreak of trichinellosis occurred in Belgium in 2014 and the ensuing investigation identified wild boar meat imported from Spain, as the source of infection (Messiaen et al., 2016). Other human outbreaks associated with consumption of wild boar meat have been widely reported worldwide (De et al., 2015; Holzhauer et al., 2014; Kim et al., 2011; Rózycki et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the majority of cases of human trichinellosis have been caused by the consumption of the infected meat of wild boars, which are hunted illegally and not examined for the presence of Trichinella spp. [ 9 , 10 , 11 ]. The increasing percentage of infected wild boars poses further risks to humans.…”
Section: Introductionmentioning
confidence: 99%